Cahsless Society on GoPay: An Islamic Economic Perspective - Zafani, Dita; Arifqi, Moh. Musfiq (Journal of Islamic Economic Laws, 2020)
Technological developments have led to massive Cashless Society activities among the public, especially in GoPay transactions. Indonesian people, who are predominantly Muslim, have started to shift their payment system from cash to cashless transactions. Therefore, the study of Islamic economics is important to see this phenomenon. The qualitative-descriptive research methodology was used by researchers to examine this research. A standard general procedure of library research is done to obtain data from several scientific papers in the form of books, magazines, journals, articles, documentation and other relevant media. The results of this study state that the Cashless Society's activities through GoPay transactions can be said to be in accordance with the principles of Islamic economics. This can be proven in the transaction that there is no party that loses money between the customer and the service provider, and there is no interest in the transaction. In addition, the Cashles Society can provide convenience in transactions between economic actors, as well as a more reliable guarantee of security.